Evaluation Of Radiomorphological Changes On Panoramic Radiography In Defense Athletes - Kübra Başaran Aslan; Burak Erdinç Aslan; Binali Çakır (Current Research in Dental Sciences)
AbstractObjective The alveolar prominence can change the morphology of the mandible by showing continuous remodeling. The chronic remodeling/resorption process of the jaw is influenced by gender, genetics, systemic conditions, sequence of tooth loss, duration of edentulism and other unknown factors. Our aim in this study is to investigate the effect of continuous trauma to the maxillofacial region on the morphology of the mandible in defense athletes.Methods: In the study, the patients who applied to the Atatürk University of Dentistry, Department of Oral, Dental and Maxillofacial Radiology and routine panoramic radiographs of 26 athletes who have been involved in defense sports such as boxing, kickboxing, and karate for at least 5 years were used. Measurements were made using various parameters on the printouts of these graphs and the values of the right and left sides were compared.Results: When the condyle height, ramus height, gonial angle and antegonial angle parameters are evaluated, there is a significant relationship between right and left values. Condyle index, Ramus index and Condylar ramus index values show no asymmetry in defense athletes.Conclusion: In defense athletes were exposed to constant trauma; neither age, duration of sports, nor exposure to maxillofacial trauma did not cause significant changes in mandible morphology.Keywords: Athletes, trauma, morphology, facial asymmetry